Inside Front Cover Image, Volume 1, Issue 3, July 2022. Issue 3 (20th July 2022) - Unknown
Abstract : Inside Front Cover : The natural environment is chosen as the background since the development of high‐performance Li‐S batteries helps to reduce the adverse impact on the environment. The single battery in the middle is the schematic diagram of lithium sulfur battery, mainly containing sulfur cathode with functional binder, electrolyte, separator and lithium anode. In the electrolyte section between sulfur cathode and separator, the chains with more than four spheres represent polysulfide dianions, while the chains with no more than four spheres represent polysulfide radicals. Noting that these polysulfides do not exist in the electrolyte section toward lithium metal anode illustrate the excellent ability of the as‐developed binder to suppress polysulfide shuttle effect. The molecular structure of functional binder is listed, which is simplified to chain structure with cucurbit. The cucurbit vines represent the amide and ‐NH2 groups that can capture polysulfides (Sx 2‐, purple balls). And the cucurbit on side chain represents the functional disulfide quinary ring that can capture polysulfide radicals (Sn ‐, yellow balls).